Layanan Informasi Karir Sebagai Prediktor Kemandirian Pemilihan Karir - Styorini, Indyah Novi (Universitas Persatuan Guru 1945 NTT, 2018)
The purpose of this research is to know the influence of career information service against the autonomy of the career choice of students at grade XI SMA Sudirman Kupang. This research is a study of empirical research that aims to provide answers to the question why with explaining the reason of occurrence of a phenomenon. In this study, which became population are students grade XI SMA Sudirman Kupang that the amounts are 45 students, while the technique of sample used in this study is the saturation sample, meaning the overall use of members within a population, which means in this study involved 45 students as a sample. Results of the study show that there is a positive and significant influence among the career information service with the autonomy of career choice of students.